2014
DOI: 10.1039/c4fo00068d
|View full text |Cite
|
Sign up to set email alerts
|

Kaempferol attenuates the glutamate-induced oxidative stress in mouse-derived hippocampal neuronal HT22 cells

Abstract: It is thought that the neuronal cell loss caused by oxidative stress is the primary mechanism underlying the pathogenesis of several neurodegenerative disorders. Glutamate is an endogenous neurotransmitter, but at high concentrations it can act as a neurotoxicant by increasing the intracellular levels of reactive oxygen species (ROS). Therefore, the development of factors that can attenuate glutamate-induced oxidative stress in neuronal cells is a good strategy by which new drugs could be discovered that may t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(54 citation statements)
references
References 36 publications
2
52
0
Order By: Relevance
“…Actually, oxidative injury was previously reported to be triggered in HT22 cells under glutamate stimulation, and the medicinal herb Gastrodia elata remarkably prevented oxidative glutamate toxicity (Han et al 2014). Besides, several previous investigations illustrated that suppression of ROS production by various substances such as kaempferol (Yang et al 2014), acetogenin A (Lee et al 2015), pinacidil (Shukry et al 2015), or herbal mixture (Ahn et al 2015) could remarkably attenuate cell apoptosis in mouse hippocampal HT22 cells. Similarly, results from our current study illustrated that HupA pretreatment dramatically suppressed ROS accumulation and subsequent neuronal damage in HT22 cells.…”
Section: Discussionmentioning
confidence: 97%
“…Actually, oxidative injury was previously reported to be triggered in HT22 cells under glutamate stimulation, and the medicinal herb Gastrodia elata remarkably prevented oxidative glutamate toxicity (Han et al 2014). Besides, several previous investigations illustrated that suppression of ROS production by various substances such as kaempferol (Yang et al 2014), acetogenin A (Lee et al 2015), pinacidil (Shukry et al 2015), or herbal mixture (Ahn et al 2015) could remarkably attenuate cell apoptosis in mouse hippocampal HT22 cells. Similarly, results from our current study illustrated that HupA pretreatment dramatically suppressed ROS accumulation and subsequent neuronal damage in HT22 cells.…”
Section: Discussionmentioning
confidence: 97%
“…However, excessive ROS can be detrimental to cells as a result of induction of oxidative stress and cellular damage [41]. Earlier studies describing the chronic effect of glutamate exposure in cellular toxicity point to the crucial role of oxidative stress-induced ROS as a major stimulus of glutamate-induced cell death [17, 4245]. It has been reported that excessive concentrations of extracellular glutamate antagonize the glutamate/cystine-antiporter and inhibit cystine uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Paraquat has been reported to cause brain damage via formation of oxygen-free radicals (60), leading to neuronal cell death that finally causes disease. Glutamate, an endogenous neurotransmitter, in high concentrations acts as a neurotoxicant by increasing intracellular ROS levels (62). Glutamate-induced oxidative stress plays an im- portant role in neuronal cell injury and degeneration in many brain disorders (16,33).…”
Section: Discussionmentioning
confidence: 99%